Construction work and risk of occupational disability: a ten year follow up of 14 474 male workers. Issue 8 (26th July 2005) - Arndt, V; Rothenbacher, D; Daniel, U; Zschenderlein, B; Schuberth, S; Brenner, H
Abstract : Aims: Most industrialised countries have public income maintenance programmes to protect workers in case of disability but studies addressing disability risk of specific professional groups are rare. The objective of this study was to establish a detailed pattern of the nature and extent of occupational disability among construction workers. Methods: A cohort study was set up including 14 474 male workers from the construction industry in Württemberg (Germany) aged 25–64 years who underwent occupational health exams between 1986 and 1992. The cohort was linked to the regional pension register of the manual workers' pension insurance institution to identify workers who were granted a disability pension during the 10 year follow up. All-cause and cause specific standardised incidence ratios (SIR) and 95% confidence intervals (CI) were calculated using disability rates from the general workforce and from all blue collar workers in Germany as references. Results: In total, 2247 (16%) members of the cohort were granted a disability pension. Major causes of disability were musculoskeletal (45%) and cardiovascular diseases (19%). In comparison with the general workforce, construction workers experienced a higher risk of disability from cancer (SIR = 1.26; 95% CI 1.08 to 1.47), respiratory diseases (SIR = 1.27; 95% CI 1.03 to 1.55), musculoskeletal diseases (SIR = 2.16; 95% CI 2.03 to 2.30), injuries/poisoning (SIR = 2.52; 95% CI 2.06 to 3.05), and all causes combined (SIR = 1.47; 95% CI 1.41 to 1.53). When compared with the blue collar reference group, increased risks of disability among construction workers were found for musculoskeletal diseases (SIR = 1.53; 95% CI 1.44 to 1.63), injury/poisoning (SIR = 1.83; 95% CI 1.50 to 2.21), and all causes combined (SIR = 1.11; 95% CI 1.07 to 1.16). Conclusions: Musculoskeletal diseases and external causes are major factors limiting the work capability of construction workers and lead to an increased proportion of occupational disability.